Stress - An overview - Mahmud, Arif; Azad, Alya Fardous (Pulse, 2022)
Background: Stress can be described as a circumstance that disturbs or is likely to disturb the normal physiological or psychological functioning of a person. It may seem that there's nothing one can do about stress. But in fact the control can be more than one can think about. Objective: Create awareness about psychological support in work-life balance, reduced stress levels at work and at home, greater focus and concentration, participate more fully in family and social life, pursue personal goals and hobbies, improved health. Conclusion: The simple realization that one can be in control of his/her life is the foundation of stress management. Pulse volumel.11 January-December 2018-2019 p.4-6